2010
DOI: 10.1038/nmeth0910-681
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry in high-throughput proteomics: ready for the big time

Abstract: Mass spectrometry has evolved and matured to a level where it is able to assess the complexity of the human proteome. We discuss some of the expected challenges ahead and promising strategies for success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
389
1
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 444 publications
(396 citation statements)
references
References 43 publications
2
389
1
3
Order By: Relevance
“…Comprehensive studies on the proteomes of cells, tissues, or organisms have been reported (e.g. Addona et al , 2009; Nilsson et al , 2010; Beck et al , 2011; Nagaraj et al , 2011; for review, see Bensimon et al , 2012; Kulak et al , 2014; Wilhelm et al , 2014; Hein et al , 2015; Richards et al , 2015), but accurate quantitative information on proteins expressed at low levels remains scarce. As a consequence, published estimates for the abundance of specific proteins sometimes vary over several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive studies on the proteomes of cells, tissues, or organisms have been reported (e.g. Addona et al , 2009; Nilsson et al , 2010; Beck et al , 2011; Nagaraj et al , 2011; for review, see Bensimon et al , 2012; Kulak et al , 2014; Wilhelm et al , 2014; Hein et al , 2015; Richards et al , 2015), but accurate quantitative information on proteins expressed at low levels remains scarce. As a consequence, published estimates for the abundance of specific proteins sometimes vary over several orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…25 Recently, some researches based on microarray and label-free quantification method have been found to be valuable for the understanding of miRNAs and their target interactions; even though microarray technology suffers from limitations in sensitivity and specificity, 26 and also the sensitivity of most proteomic analysis based on label-free quantification method by spectrometers is modulated by the nature of the processed samples. 27 In this research, we improve the sensitivity of miRNA and protein identification by deep sequencing and iTRAQ quantitative proteomics respectively. A novelty of our research is that we identified more than one hundred potential miRNA-target pairs from computationally predicted targets, considering a negative relationship of the expression patterns between miRNA and their target protein is the most important parameter for accessing their interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Although proteins can be reliably identified by the well known discovery proteomics methods at high throughput 11 and their 3D structures can be determined experimentally or computationally 12, there remain numerous unsolved problems relating to their structure and function in the context of network biology. Measuring proteins poses technical challenges, particularly in higher eukaryotes which are made‐up of trillions of cells that are categorized, somewhat arbitrarily, into more than 400 different cell types 13.…”
Section: Introductionmentioning
confidence: 99%